2004
DOI: 10.1111/j.1365-313x.2004.02017.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered activity of the P2 isoform of plastidic glucose 6‐phosphate dehydrogenase in tobacco (Nicotiana tabacum cv. Samsun) causes changes in carbohydrate metabolism and response to oxidative stress in leaves

Abstract: SummaryExpression of one speci®c isoform of plastidic glucose 6-phosphate dehydrogenase (G6PDH) was manipulated in transgenic tobacco. Antisense and sense constructs of the endogenous P2 form of G6PDH were used to transform plants under the control of the cauli¯ower mosaic virus (CaMV) 35S promotor. Recombinant plants with altered expression were taken through to homozygosity by selective screening. Northern analyses revealed substantial changes in the expression of the P2 form of G6PDH, with no apparent impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…The picture is, however, not fully clear. For example, although transgenic experiments in which glucose-6-phosphate dehydrogenase was overexpressed in tobacco leaves indicate that the enzyme plays a role in determining the ratio of starch to soluble sugars (25), it is not known whether this contribution extends to amyloplasts.…”
Section: Ko Of Ntrc Strongly Decreases Redox Activation Of Root Agpasmentioning
confidence: 99%
“…The picture is, however, not fully clear. For example, although transgenic experiments in which glucose-6-phosphate dehydrogenase was overexpressed in tobacco leaves indicate that the enzyme plays a role in determining the ratio of starch to soluble sugars (25), it is not known whether this contribution extends to amyloplasts.…”
Section: Ko Of Ntrc Strongly Decreases Redox Activation Of Root Agpasmentioning
confidence: 99%
“…Additionally, redox regulation and product inhibition participate in modulating G6PD activity (Wendt et al, 2000;Debnam et al, 2004;Schürmann and Buchanan, 2008). It is interesting to note that G6PD6 was shown to be inactivated by oxidation (Wakao and Benning, 2005) and that total G6PD activity was reduced in salt-stressed aska mutants.…”
Section: Discussionmentioning
confidence: 99%
“…In plants, G6PD activity is present in the plastids and cytosol (Debnam and Emes, 1999). G6PD activity has been positively correlated with environmental stresses such as salt stress (Valderrama et al, 2006;Wang et al, 2008), aluminum toxicity (Slaski et al, 2006), drought (Scharte et al, 2009), and infection by viral and fungal pathogens (Sindelár and Sindelárová, 2002;Scharte et al, 2009); by contrast, a decrease in chloroplastic G6PD activity has been shown to be beneficial for withstanding oxidative stress (Debnam et al, 2004). Thus, the role of G6PD in the stress response is currently unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…G6PD activity can be regulated by the cellular redox status, the NADPH-NADP + ratio, and protein phosphorylation (Wendt et al, 2000;Debnam et al, 2004;Schürmann and Buchanan, 2008;Dal Santo et al, 2012). Under high-salinity conditions, G6PD activity is regulated by the Arabidopsis protein kinase ASKa.…”
mentioning
confidence: 99%